3D Woven Near‐Net‐Shape Preforms for Composite Structures1 . Issue 3 (19th November 2015) - Mountasir, Adil; Löser, Michael; Hoffmann, Gerald; Cherif, Chokri; Großmann, Knut
Abstract : Weaving of near‐net‐shape spacer structures is an efficient way to produce preforms for fiber‐reinforced composites. The preforms are woven using non‐crimp fiber arrangement in warp and weft directions. For getting a better insight into the weaving process as well as to analyze warp thread forces, a simulation model has been developed. This enables calculations under variation of machine and process parameters to minimize warp thread forces. The aim in conjunction with this is downsizing the tensile stress of threads for reducing fiber damage. The high potential of the non‐crimp fiber arrangement is demonstrated in consolidated 2D composite sheets and 3D spacer composites. Abstract : The paper deals with manufacturing technology for non‐crimp woven fabrics and simulation of weaving process . The aim of the corresponding research is to ensure a reproducible manufacturing and to ensure mechanical properties of the produced composite structures. The mechanical properties of composites have been tested and the results are presented.